Molarity effect on the structural properties of Nano-MgO thin films / Habibah Zulkefle ... [et al.] - Zulkefle, Habibah; Ismail, Lyly Nyl; Abu Bahar, Raudah; Mahmood, Mohamad Rusop (Scientific.Net, 2011)
Nano-MgO thin films were grown on the cleaned glass substrate via sol-gel spin coating techniques using magnesium acetate tetrahydrate, ethanol and nitric acid. For the thin films deposition, the solutions were prepared at six different molar concentrations (0.1M, 0.2M, 0.4M, 0.6M, 0.8M and 1M). The thickness and roughness of nano-MgO films was found to be increased with an increase of molar concentration. The increment in particle size and agglomerated particles were observed from FESEM (JEOL JSM-J600F) images as the molar concentration increased from 0.1M to 1.0M. The results showed 0.4M nano-MgO films have the best properties for example it has a uniform film, non-porous structure and has nanometer dimension size which around 42.8nm.